Characteristics of Passive Films Formed on As-Cast Ti–6Al-4V in Hank’s Solution Before and After Transpassivation - Yi, Guo; Liu, Xinxin; Zheng, Chuanbo; Zhang, Hongyue; Xu, Cheng; Cui, Yu-Wei; Liu, Shuan (Frontiers in Materials, 2021)
In this work, the characteristics of passive films formed on as-cast Ti-6Al-4V before and after transpassivation by electrochemical methods. Simulated body fluid of Hank’s solution was used as the electrolyte in this work. According to the potentiodynamic polarization test, the passivation range, transpassive range, and re-passivation range of as-cast Ti-6Al-4V were obtained. Afterward, the potentiostatic polarization was employed to passivate the Ti-6Al-4V in both passivation and re-passivation ranges. Electrochemical impedance spectroscopy (EIS) was used to analyze the characteristics of formed passive films. Different electrochemical behavior of as-cast Ti–6Al-4V is found in passivation and re-passivation ranges. The passivation current density of the sample in re-passivation range is significantly larger than that in passivation range. Meanwhile, the growth rate of passive film in re-passivation range is also greater than that in passivation range. Although the sample shows a higher charge transfer impedance in the re-passivation range, metastable pitting corrosion is also observed, indicating the formation of the unstable passive film. Such results advance the understanding of as-cast Ti-6Al-4V polarized under different potentials for potential biomedical applications.